Microstructural phase coexistence kinetics near the polymorphic phase boundary. (March 2021) - Torres-Matheus, Oscar A.; García, R. Edwin; Bishop, Catherine M.
Graphical abstract: Abstract: By implementing a novel multiphase field model for ferroelectric systems, the phase coexistence of the tetragonal (T) and rhombohedral (R) phases in Pb-free BZT-40BCT was analyzed. Metastable coexistence of the T and R phases is predicted between a thermodynamic upper limit at T C, R = 49.90 ∘ C and a kinetic lower limit determined by the time-temperature-transformation behaviour. Predicted domain microstructures exhibit faceted domain walls and curved T-R phase interfaces that are consistent with recent TEM studies in the vicinity of the polymorphic phase boundary (PPB). Further, miniaturization of the domain structure near the PPB is a result of the relatively low interfacial energies and a pinning effect caused by the large metastable phase fraction that originates from the vanishing macroscopic driving force for phase transformation. Particularly, the vanishing of rhombohedral domain wall energies as T → T C, R enables a phase transformation-induced polarization rotation mechanism and predicts a hierarchical domain morphology for the R phase. These results are in agreement with the higher piezoelectric response reported near the maximum temperature for R+T coexistence and the observations of a miniaturized nanodomains structure within micron-sized, wedge-shaped domains in the R phase for the BZT- x BCT system.